EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE DENGAN METODE QUESTION STUDENT HAVE DAN THINK TALK WRITE PADA POKOK BAHASAN BANGUN RUANG DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS VIII SMP NEGERI SE-KABUPATEN SLEMAN TP 2013/2014 - Asy’ari, Asy’ari; Usodo, Budi; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objektive of this research was to investigate the effect of the learning models on the learning achievement in mathematics viewed from learning independence of the students. The learning models compared were the TPSq learning model with the question student have method, the TTW learning model, and the conventional learning model. This study was a quasi-experimental study with a 3Ã3 factorial design. The study population was all of grade VIII students of State Junior Secondary School in Sleman regency. Sampling was done by stratified cluster random sampling. The samples in this study amounted to 262 students with the details of 87 students for experiment 1 and 87 for experiments 2 and 88 for the control class. The data collected instrument used mathematics achievement tests and a questionnaire of studentâs learning Â independence. Based on the hypothesis testing can be concluded as follows. (1) The learning achievement of the students treated with TPSq learning modelÂ with the question student have method was as good as that ofÂ those with the TTW learning model. In addition, studentsâ learning achievement treated by TPSq model with question student have method and TTW better than students treated by conventional learning model. (2) Studentsâ learning achievement which has high learning independence had better achievement than students who have moderate and low independence. In addition, students who have moderate learning independence had better achievement than students who have low learning independence. (3) In the TPSq learning model with the question student have method, TTW and conventional learning model, the studentsâ learning achievement who have high learning independence had better achievement than moderate and low learning independence, in addition the studentsâ learning achievement who have moderate learning independence had better achievement than students who have low learning independence. (4) In the learning independence category of high, moderate or low, the learning achievement of the students treated with TPSq learning model with the question student have method and TTW learning model was equally good. In addition, studentsâ learning achievement treated by TPSqÂ learning model with the question student have method and TTW learning model had better achievement than students treated by conventional learning model.Keywords: Think Pair Square (TPSq), Question Student Have, Think Talk Write (TTW), and Studentâs Learning Independence.